2010
DOI: 10.3892/mmr_00000290
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neoplastic effect of β-hydroxyisovalerylshikonin on a human choriocarcinoma cell line

Abstract: Abstract.β-hydroxyisovalerylshikonin (β-HiVS), a compound isolated from the traditional asian medicinal herb Lithospermum radix, is an aTP non-competitive inhibitor of protein-tyrosine kinases such as v-Src and eGFr, and has been shown to induce apoptosis in several human tumor cell lines. We investigated the effect of β-HiVS in the choriocarcinoma cell line, BeWo. BeWo cells were treated with various concentrations of β-HiVS, and changes in cell growth, the cell cycle, apoptosis, and related parameters were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…When 10 −6 M β-HIVS was used to treat HL-60 cells for 3 h, typical apoptotic characteristics were observed in the cells, including morphological changes, nuclear fragmentation, DNA ladder formation and caspase-3 activation, which indicates that β-HIVS induced tumor cell apoptosis through a caspase-3-dependent mechanism. Previous studies ( 28 , 31 ) verified that β-HIVS exerted inhibitory and proapoptotic effects on endometrial cancer, chorionic carcinoma and ovarian cancer cells, with IC 50 values ranging between 10 −6 and 10 −8 M.…”
Section: Discussionmentioning
confidence: 85%
“…When 10 −6 M β-HIVS was used to treat HL-60 cells for 3 h, typical apoptotic characteristics were observed in the cells, including morphological changes, nuclear fragmentation, DNA ladder formation and caspase-3 activation, which indicates that β-HIVS induced tumor cell apoptosis through a caspase-3-dependent mechanism. Previous studies ( 28 , 31 ) verified that β-HIVS exerted inhibitory and proapoptotic effects on endometrial cancer, chorionic carcinoma and ovarian cancer cells, with IC 50 values ranging between 10 −6 and 10 −8 M.…”
Section: Discussionmentioning
confidence: 85%
“…Beta-HIVS is an ATP non-competitive inhibitor of protein-tyrosine kinases and is capable of inducing apoptosis in various lines of human tumor cells which has been documented by several publications [9][10][11][12][13][14][15][16]. Hashimoto et al, 2002 found that beta-HIVS was able to induce cell death more efficiently in DMS114 and NCI-H522 lung cancer cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…Μία άλλη οδός για την καταπολέμηση του καρκίνου είναι και η αναστολή της αγγειογένεσης. Η σικονίνη έχει μελετηθεί ως πιθανός αναστολέας της αγγειογένεσης (Hisa et al, 1998) (Bhatia et al, 2011;Takai et al, 2010;Xiong et al, 2009). Ανάλογη έρευνα μελέτησε την αντικαρκινική δράση αλκαννίνης και εστέρων της, που απομονώθηκαν από ρίζες του φυτού Alkanna cappadocica, έναντι δώδεκα ανθρώπινων καρκινικών σειρών με ιδιαίτερα ενθαρρυντικά αποτε-λέσματα (Sevimli-Gur et al, 2010).…”
Section: αντιμικροβιακή δράσηunclassified